Ancistrocladinium A Induces Apoptosis in Proteasome Inhibitor-Resistant Multiple Myeloma Cells: A Promising Therapeutic Agent Candidate - Daniela Brünnert; Raina Seupel; Pankaj Goyal; Matthias Bach; Heike Schraud; Stefanie Kirner; Eva Köster; Doris Feineis; Ralf C. Bargou; Andreas Schlosser; Gerhard Bringmann; Manik Chatterjee (MDPI AG, 2023)
The N,C-coupled naphthylisoquinoline alkaloid ancistrocladinium A belongs to a novel class of natural products with potent antiprotozoal activity. Its effects on tumor cells, however, have not yet been explored. We demonstrate the antitumor activity of ancistrocladinium A in multiple myeloma (MM), a yet incurable blood cancer that represents a model disease for adaptation to proteotoxic stress. Viability assays showed a potent apoptosis-inducing effect of ancistrocladinium A in MM cell lines, including those with proteasome inhibitor (PI) resistance, and in primary MM cells, but not in non-malignant blood cells. Concomitant treatment with the PI carfilzomib or the histone deacetylase inhibitor panobinostat strongly enhanced the ancistrocladinium A-induced apoptosis. Mass spectrometry with biotinylated ancistrocladinium A revealed significant enrichment of RNA-splicing-associated proteins. Affected RNA-splicing-associated pathways included genes involved in proteotoxic stress response, such as PSMB5-associated genes and the heat shock proteins HSP90 and HSP70. Furthermore, we found strong induction of ATF4 and the ATM/H2AX pathway, both of which are critically involved in the integrated cellular response following proteotoxic and oxidative stress. Taken together, our data indicate that ancistrocladinium A targets cellular stress regulation in MM and improves the therapeutic response to PIs or overcomes PI resistance, and thus may represent a promising potential therapeutic agent.